DESIGN & DEVELOPMENT OF A MULTI-PATH DYNAMIC ROUTING ALGORITHM FOR HIGH DATA INTEGRITY - Bharghavi, M; Dimlo, U M Fernandes; Rani, A Shobha; Someswar, G Manoj (Compusoft: an international journal of advanced computer technology, 2017)
Applications running on the same Wireless Sensor Network (WSN) platform usually have different Quality of Service (qos) requirements. Two basic requirements are low delay and high data integrity. However, in most situations, these two requirements cannot be satisfied simultaneously. In this research paper, based on the concept of potential in physics, we propose IDDR, a multi-path dynamic routing algorithm, to resolve this conflict. By constructing a virtual hybrid potential field, IDDR separates packets of applications with different qos requirements according to the weight assigned to each packet and routes them towards the sink through different paths to improve the data fidelity for integrity-sensitive applications as well as reduce the endto-end delay for delay-sensitive ones. Using the Lyapunov drift technique, we prove that IDDR is stable. Simulation results demonstrate that IDDR provides data integrity and delay differentiated services.